THE HISTORY OF FIEP IN ARGENTINA (Fiep Bulletin - online, 2013)
Professor Enrique Carlos Romero Brest was born in Buenos Aires on the 9th of November, 1902. He graduated in Physical Education from the Higher National Institute of Physical Education in 1921 and in Natural Sciences from the Normal School Mariano Acosta the following year. He became a Graduate Physical Education Professor from the Higher National Institute of Physical Education in Buenos Aires in 1921 and a Graduate Science Teacher from the Normal School Mariano Acosta in Buenos Aires in 1992. He received numerous academic honors and awards during his long career and was a member and held positions in international bodies and associations. He participated in these associations and bodies, held numerous positions as a teacher in various educational institutions in Buenos Aires and was officially invited as a consultant and lecturer by various international institutions. Professor Enrique Carlos Romero Brest lectured extensively and was the author of a large number of works which amount to some 160 publications among books and papers. In addition, he has had 44 working papers and presentations in congresses, 49 memorials to authorities, 119 technical reports prepared in the course of his official duties, and edited 26 works from the collection Library of Physical Education Publishers of Editorial Paidós. He was also director of the Physical Education Journal of the National Institute of Physical Education. He was the creator of national and international institutions such as the South American Confederation of Physical Education Teachers Associations in 1950, Pan American Physical Education Confederation, South American Planning Committee of Pan American Congresses in 1950 and the South American Volleyball Confederation in 1946. Professor Brest had outstanding performances in various national and international conferences since 1934, and it is in 1949 when he attends the Stockholm Congress in Sweden that he gets in touch with FIEP and becomes the first FIEP National Delegate of Argentina, a position he held until 1969. Professor Carlos Enrique Romero Brest died in 1985. This summary has been based on data provided by Professor Filimer Ferro of the Physical Education Institute Nº 1 Buenos Aires.